Monitoring the Agri-food System in Myanmar: The rising costs of diets and declining purchasing power of casual wage laborers: December 2021–November 2023 - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
We assess changes in food prices and purchasing power of casual wage laborers based on large-scale surveys of households and food vendors (fielded from December 2021 until November 2023) in rural and urban areas and in all state/regions of Myanmar. Key Findings: • Over the survey period (December 2021–November 2023), the cost of the healthy diet rose by 93 percent and the common diet by 103 percent. • After a reprieve from high food inflation in the first half of 2023, prices increased rapidly in the latter part of 2023, resulting in a 28 and 35 percent increase in the cost of healthy and common diets in September–November 2023 compared to a similar period in 2022, when food prices were already very high. • Prices of rice—the major staple—increased by 75 percent between October–December 2022 and September–November 2023, and were the main driver of the 35 percent increase in the cost of the common diet. • Over the full period of surveys (December 2021–November 2023), onion prices quadrupled; rice prices more than doubled; oil and pulse prices doubled; and all other food prices increased by at least 50 percent. • The purchasing power of daily urban construction wages relative to healthy diet costs declined by 11 percent and by 15 percent relative to common diet costs. The purchasing power of rural agricultural wages relative to the healthy diet held steady but fell by 7 percent relative to common diet costs. • Food costs outpaced wages, particularly in urban areas, making food increasingly unaffordable for wage earners who are among the most vulnerable household groups in Myanmar. However, nominal wages rose at a faster pace in 2023 compared to 2022, slowing the pace of declining real wages. Recommended Actions • Actions should be taken to reduce the prices of nutritious foods in a sustainable and market oriented manner. • As casual wage workers are among the poorest and as their situation is worsening, they should be targeted in social safety net programs.